Speech language pathology Clinical Education: perceptions and experiences of clinical educators and students - Rocha, Joana Antonieta; Oliveira Santos, Catarina; Peixoto, Vânia; Maia, Fátima; Gama Alegria, Rita (Revista de Investigación en Logopedia, 2020)
For the purposes of professional development clinical education is crucial to speech-language pathologists (SLP). There is limited information about clinical education of SLP students in Portugal. The aim of this study was to describe and compare the mutual perceptions of Portuguese SLP’s clinical educators and students’ of SLP in a Portuguese private University Clinic. Five SLP clinical educators and nine students participated in a one on one semi-structured interview. Content analysis was used to explore interview data. The analysis led to the identification of four themes shared by both groups. Findings from this study provided an insight about clinical education characteristics and challenges reported by clinical educators and students in Portugal and to compare those results with others mentioned in other countries. The findings of this study suggest that clinical educators and students identify, in general, similar characteristics regarding effective/non-effective clinical educator profile and benefits regarding clinical education process. The sample provides preliminary data on Portuguese clinical educator’s and student’s experience of clinical education.